Piacere! Elementary Italian at The University of Iowa - Gemmani, Lucia; Lottini, Irene; Sartini-Rideout, Claudia (Open textbook library., 2023)
Piacere! is an elementary Italian open-access textbook authorized by the Italian faculty of The University of Iowa. A comprehensive and flexible e-textbook, this Open Education Resource aims to support students’ acquisition of the grammar and vocabulary that ensure meaningful communication as well as to enhance students’ familiarity with Italian culture. Piacere! is divided into twenty-one units, which revolve around a specific theme, in order to facilitate a comprehensive learning and use of the language. Units include the following components: grammar, vocabulary, conversations, and readings. While in its organization the textbook is meant to offer the students with a flexible and approachable individual study experience, each component may be easily translated into classroom activities.